FluMob: Enabling Surveillance of Acute Respiratory Infections in Health-care Workers via Mobile Phones - Lwin, May Oo; Yung, Chee Fu; Yap, Peiling; Jayasundar, Karthikayen; Sheldenkar, Anita; Subasinghe, Kosala; Foo, Schubert; Jayasinghe, Udeepa Gayantha; Xu, Huarong; Chai, Siaw Ching; Kurlye, Ashwin; Chen, Jie; et al. (Frontiers in Public Health, 2017)
Singapore is a hotspot for emerging infectious diseases and faces a constant risk of pandemic outbreaks as a major travel and health hub for Southeast Asia. With an increasing penetration of smart phone usage in this region, Singapore’s pandemic preparedness framework can be strengthened by applying a mobile-based approach to health surveillance and control, and improving upon existing ideas by addressing gaps, such as a lack of health communication. FluMob is a digitally integrated syndromic surveillance system designed to assist health authorities in obtaining real-time epidemiological and surveillance data from healthcare workers (HCW) within Singapore, by allowing them to report influenza incidence using smartphones. The system, integrating a fully responsive web-based interface and a mobile interface, is made available to HCW using various types of mobile devices and web browsers. Real-time data generated from FluMob will be complementary to current healthcare and laboratory based systems. This paper describes the development of FluMob, as well as challenges faced in the creation of the system.